INSTITUSI PENGAWASAN PUBLIK (HISBAH) MENURUT IBNU TAIMIYAH - Hajar, Elvira Sitna (An Nawawi, 2021)
The book "Al-Hisbah fi al Islam" is a classic because it was written 700 years ago by Shaykh Ibn Taimiyah, but its relevance is still felt today. There are many discussions that are beyond their time and are increasingly evident in their urgency in modern times. This shows that the verses of the Qur'an and the Hadith of the Prophet Muhammad which are the main references are eternal and become the guidelines of human life throughout the ages. Hisbah can be defined as an institution for monitoring and controlling commodity prices in the market (price control) as well as monitoring the behavior of government officials. What is special about his work is that it does not only refer to texts as normative sources but also follows the history and practice of the people around him. So that apart from being scientifically qualified, new findings can also be discussed in the field. Although Ibn Taimiyah is known as an expert in kalam and fiqh, the book talks about public duties and market economy (issues that are the main concern of modern society today).